Studing daughter cell line in Cryptosporidium spp.In vitro culturing - Jaber Aowda Kadhim (Al-Qadisiyah Journal of Pure Science, 2018)
This study was designed to see the ability of Cryptosporidium Spp. to grow and  develop in  stem cells from human placenta because this could have series transmission implications in relation to pregnant human and other vertebrate hosts,Cryptosporidium was cultured successfully for the first time in human placental stem cells from ( chorion, aminion, umbilical cord ) and mice bone marrow stem cells, with rate of 22,20,16,10%  respectively comparing with 24%  in mice peritoneal macrophages,both sexual and a sexual reproductions was occurred in cultured stem cells and the produced oocysts were seen free within the culture media,this result is represent the first time for recording the parasite growth in placental stem cells and this will opena gate for more intracellular parasites culturing and promise a source of available and abundant undifferentiated  cells for other researches.